Ministry of Civil Aviation Decree No. 218 of the Year 2019 Issued on 27/2/2019 = وزارة الطيران المدنى قرار رقم 218 لسنة 2019 الصادر فى 27/2/201 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic